Optimalisasi Potensi Cuka Salak sebagai Basis Pengembangan Produk Olahan Salak di Wonokerto, Turi, Sleman: Optimization of Snake Fruit Vinegar Potential as a Basis for Developing Snake Fruit Processed Products in Wonokerto, Turi, Sleman - Julianto, Tatang Shabur; Muhaimin, Muhaimin; Virgiawan, Rheyza (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This community service program aimed to empower the local potential of salak fruit in Wonokerto Village, Turi Subdistrict, Sleman Regency, by developing salak vinegar as a value-added product. The community has traditionally sold salak in its fresh form, which provides low economic value and is vulnerable to price drops during peak harvest seasons. Limited knowledge of fermentation techniques, product quality standards, business management, and marketing has been a major obstacle to the development of processed salak products. The program was carried out from September to December 2023 through several stages, including site surveys, training on salak vinegar production, hands-on fermentation practice, product evaluation, and assistance in obtaining household food industry (PIRT) certification. The training focused on two-stage fermentation using yeast and Acetobacter aceti, sterilization procedures, proper packaging, and digital marketing strategies. The results showed that participants were able to produce high-quality salak vinegar. Laboratory tests indicated acetic acid levels of 1.05–1.16% and pH values of 3.14–3.19, which fall within the acceptable range for edible vinegar. Organoleptic testing demonstrated positive acceptance, particularly in aroma and color. Furthermore, assistance in PIRT licensing and marketing enhancement increased the product's readiness to enter the market. Overall, the program successfully improved community skills and knowledge in product diversification and opened new economic opportunities based on local resources. This initiative is expected to serve as a replicable model of empowerment for other salak-producing regions.